Amphiphilic Triblock Copolymer guided Polyaniline embraced CNT nanohybrid with outcropping whiskers as an energy storage electrode. (20th August 2017) - Arulmani, Subramanian; Wu, Jerry J.; Anandan, Sambandam
Graphical abstract: Abstract: Block copolymer (P-123) assisted nanohybrid of Polyaniline embraced Carbon nanotubes (PANI@CNT) with outcropping whiskers at the edge were synthesized to facilitates simple charge and ion transport at the electrode interface. Structural and morphological portrayals of the as-synthesized materials were realized by numerous techniques and their energy storage performance was electrochemically assessed. The nanohybrid electrode reveals remarkable electrochemical possessions with superior charge storage capacitance, rapid rate responsiveness and sustained cycling performance owing to its exploited chemistry and nano-architecture. Based on the insight acquired from super capacitance values, PANI@CNT nanohybrid material provided the highest capacitance of 348.9 F g −1, which is 2.7 times superior to that of CNT and 1.5 times better than that of pure PANI, suggesting that a simplistic pathway for tailoring insertion/de-insertion of ions through high roughness in electrodes. In this nanohybrid, CNTs possibly acts as a backbone material for facile electron transfer and the porous PANI perform duties for the capacitance enhancement.